Development of a Project-Based Learning Model to Improve Student Character in Higher Education - Andika, Alek; Suryadi, Ace; Hidayat, Mupid; Warlim, Warlim; Nurdin, Encep Syarief (Jurnal Moral Kemasyarakatan, 2025)
This research proposes developing an integrated project-based learning model with student character development in higher education. This approach aims to prepare students with both academic skills and strong character to face the complex demands of the real world. Through a comprehensive literature review, this research identifies a close relationship between project-based learning and student character development. The proposed learning model integrates elements of project-based learning with proven effective character development strategies. This model aims at empowering students to enhance collaboration, problem-solving, personal responsibility, self-reflection, ethics, leadership, and empathy. The novelty of this research is the importance of implementing project-based learning in learning that must be prepared by lecturers so that learning objectives are not only oriented towards student knowledge but also character building in each learning assignment. This model has to be implemented under the support of lecturers and educational institutions as well as continuous evaluation to assess its relevance and effectiveness. Through the development of this project-based learning model, educational institutions are ready for curriculum changes and students have good and positive characters to face global challenges.